Poznokeltska in rimska naselja I. st. po Kr. na mestnem območju Savarije - Gabler, Denes (Arheološki vestnik, 1996)
The major transition from the prehistoric to the Roman period has been illuminated by important excavations and topographic surveys in the urban territory of Savaria (the fortified settlements of Szentvid near Velem and Ostffyasszonyfa). As the end of these fortified settlements cannot be determined exactly, they are dated broadly to the pre- Claudian period. The small number of lowland settlements of the late La Tene period is perhaps a result of insufficient research, but it is also not excluded that the scarce settlement density could have caused the emigration of the Eravisci. The late Celtic settlements were primarily located on the borders of the territory. During the excavation of the Roman road station at Sarvar, it was possible to establish the continued production of pottery types of the La Tene D in (he Flavian period. The regular transport of goods on the Amber Road probably began to flow after the construction of a permanent legionary camp at Carnuntum. The Savaria territory was probably not settled by the Romans in the pre- Claudian period. Veterans of the legio XV Apollinaris settled it only after the foundation of the colony. Dense tombstones of Italic settlers can be noted to the east and the northeast of Savaria. The majority of the villac rusticae were also located in the same area. Autochthonic inhabitants are attested on inscriptions only in the western, hilly parts of the province. The fact that the indigenous population that also lived in the urban center was not represented on the preserved inscriptions proves that it was greatly pushed into the background. Il is possible to find tumuli and vici (village settlements) with pottery of the La Tčnc D type in the border areas.